A direct route for the preparation of Fmoc/OtBu protected iodotyrosine. Issue 27 (4th July 2018) - Steer, Andrew M.; Bolt, Hannah L.; Brittain, William D.G.; Cobb, Steven L.
Graphical abstract: Highlights: Synthesis of an orthogonally protected iodotyrosine which can be directly used in Fmoc SPPS. Iodination reaction conditions optimised. Synthesised iodotyrosine shown to be amenable to Suzuki-Miyaura cross-coupling. Abstract: Herein the synthesis of an Fmoc/O t Bu orthogonally protected iodotyrosine derivative is reported. This has been achieved via a simple two-step process in an overall 58% yield from commercially available Fmoc-Tyr( t Bu)-OH. The Fmoc/O t Bu orthogonally protected iodotyrosine was also shown to be amenable to Suzuki-Miyaura cross-coupling to deliver a novel bi-aryl tyrosine derivative.